Effect of manually assisted cough technique on cough strength in extubated patients with organophosphorus poisoning - Nandre, Bhagyasha Shamkant; Gunjal, Sambhaji B. (International Journal of Research in Medical Sciences, 2023)
Background: Organophosphate (OP) ingestion is one of the most common emergencies treated at poisoning control centers worldwide. In an extubated patient with OPP, the abdomen and chest muscles are affected, it also affects a person's ability to breathe on their own, rendering them dependent on a ventilator. Intubation weakens the abdominal muscles and diaphragm making it difficult to cough and clear the chest. A manual cough-assisted technique is used to enhance the cough strength, to help with the clearance of secretions it can be carried out in lying, side-lying, or sitting positions. Objectives were to find the effect of a manually assisted cough (MAC) technique on cough strength (Peak cough flow (PCF) and maximum expiratory pressure) in extubated patients with organophosphorus poisoning. Methods: According to the selection criteria, 50 participants extubated with organophosphorus poisoning were included. A baseline assessment was done of all individuals and MAC techniques were given. outcome measures were assessed with PCF meter and PEmax manometer. MAC techniques are given for 1 week to each patient. Results: Pre and post-intervention PCF and maximal expiratory pressure (MEP) was compared and analyzed with paired t tests and which shows an extremely significant difference with p<0.0001 which indicates significant improvement in cough strength after 1 week of MAC techniques. Conclusions: This study concluded that the MAC. Technique improved the cough strength (PCF and MEP) in extubated patients with organophosphorus poisoning.